The same old story – or not? How storytelling can support inclusive local energy policy - Mourik, R. M.; Sonetti, G.; Robison, R. A. V. (Energy Research & Social Science, 2021)
Local energy policy agendas require commonly defined desirable future visions and collective agenda-setting to spur collaborative action. However, methods designed for multi-stakeholder engagement often do not sufficiently open up deliberative processes to all voices, and efforts to envision desired futures built from current local energy challenges are usually designed by and oriented towards specialists. With this paper, we aimed to explore how the theoretical strengths of storytelling for supporting local policy processes play out in practice. We contrast what the literature states about the potential of storytelling for solving complex challenges and facilitating collaborative processes to the lessons learnt from actually using storytelling in a set of 17 multi-stakeholder workshops across 17 European countries run as part of the H2020 SHAPE ENERGY project. The workshops were each designed around a tangible local energy policy challenge. We found storytelling has unique strengths in terms of enabling significant (un)learning regarding stakeholder relationships, allowing participants to step into others’ perspectives, keeping hold of diversity, and the use of ‘we’ in stories leading to concrete future initiatives. We also note specific learnings about when these outcomes may not be achieved, for example due to fears, traditions, hierarchical structures, as well as the need for sufficient time for planning, facilitator training and stakeholder invitations. We conclude that as an innovative, playful and flexible methodology, storytelling can undoubtedly be a valuable additional tool for policymakers where there is a desire for deliberative stakeholder involvement, and appetite to tailor approaches to local contexts.
Keywords: Changements climatiques; Engagement; Réservé UdeM; Vision collective

The role of social innovation in criminal justice reform and the risk posed by proposed reforms in England and Wales - Fox, Chris; Grimm, Robert (Criminology & Criminal Justice: An International Journal, 2015)
The UK government has called for a rehabilitation revolution in England and Wales and put its faith in market testing. It hopes this will lead to greater innovation, resulting in reductions in re-offending while also driving down costs. However, many of the most innovative developments in criminal justice over recent decades have come through social innovation. Examples include restorative justice and justice reinvestment. In this article we argue that while social innovation will respond to some extent to conventional economic policy levers such as market testing, de-regulation and the intelligent use of public sector purchasing power it is not simply an extension of the neo-liberal model into the social realm. Social innovation, based on solidarity and reciprocity, is an alternative to the logic of the neo-liberal paradigm. In policy terms, the promotion of social innovation will need to take account of the interplay between government policy, social and cultural norms and individual and social capacity. Current proposals for reforming the criminal justice system may not leave sufficient scope to develop the conditions for effective social innovation.
Keywords: Europe; Réservé UdeM

Using Social Innovation as a Theoretical Framework to Guide Future Thinking on Facilitating Collaboration Between Mental Health and Criminal Justice Services - Hean, Sarah; Willumsen, Elisabeth; Ødegård, Atle; Bjørkly, Stål (International Journal of Forensic Mental Health, 2015)
Offender mental health is a major societal challenge. Improved collaboration between mental health and criminal justice services is required to address this challenge. This article explores social innovation as a conceptual framework with which to view these collaborations and develop theoretically informed strategies to optimize interorganizational working. Two key innovation frameworks are applied to the offender mental health field and practice illustrations provided of where new innovations in collaboration, and specifically co-creation between the mental health system and criminal justice system, take place. The article recommends the development of a competency framework for leaders and front line staff in the mental health system and criminal justice systems to raise awareness and skills in the innovation process, especially through co-creation across organizational boundaries.
Keywords: Co-création; Collaboration; Criminologie; Innovation sociale; Justice; Réservé UdeM; Santé

Using the ESID Model To Reduce Intimate Male Violence Against Women - Sullivan, Cris M. (American Journal of Community Psychology, 2003)
This paper describes how the Experimental Social Innovation and Dissemination (ESID) model was successfully used to reduce male violence against women in an intimate relationship. The women in the study who worked with advocates (the key feature of the program) were significantly less likely to be abused again compared to their counterparts in the control condition. They also reported a higher quality of life and fewer difficulties in obtaining community resources even 2 years after the short-term intervention. The advocacy provided consisted of five phases: assessment, implementation, monitoring, secondary implementation, and termination. Assessment collected important information on the client's needs and goals. This involved asking the women what they needed and by observing women's circumstances. In response to each unmet need identified, the advocate worked with the woman to access appropriate community resources. This was the implementation phase. The third phase involved monitoring the effectiveness of the intervention. The advocate and client assessed whether the resource had been obtained and whether it met the identified need. If it was not effective, advocates and clients initiated a secondary implementation to meet the client's needs more effectively. Termination of the intervention consisted of three components. First, advocates emphasized termination dates from the beginning of the intervention in order to prevent termination from surprising the client. Second, beginning about week seven of the 10-week intervention, advocates intensified their efforts to transfer the skills and knowledge the women had acquired throughout the course. Third, advocates left families with written “termination packets,” which contained lists of community resources, helpful tips for obtaining difficult-to-access resources, and useful telephone numbers. A total of 143 women participated in the experimental condition, and women in the control group were not contacted again until their next interview; they received services-as-usual. 30 references
Keywords: Criminologie; Expérimentation; Innovation sociale; Réservé UdeM; Soutien social; États-Unis